Angiotensin I-converting enzyme (ACE) inhibition and nitric oxide (NO)-mediated antihypertensive effect of octaphlorethol A isolated from Ishige sinicola: In vitro molecular mechanism and in vivo SHR model. (October 2015) - Ko, Seok-Chun; Jung, Won-Kyo; Kang, Sung-Myung; Lee, Seung-Hong; Kang, Min Cheol; Heo, Soo-Jin; Kang, Kyong-Hwa; Kim, Yong-Tae; Park, Sun-Joo; Jeong, Yoonhwa; Kim, Misook; Byun, Hee-Guk; et al.
Highlights: OPA exhibited potential ACE inhibition and NO production. OPA activates eNOS by activating Akt and AMPK pathway. OPA inhibits ACE activation by the Pi interaction with ACE. Oral administration of OPA lowers blood pressure in SHR. Abstract: Angiotensin I-converting enzyme (ACE) inhibition and nitric oxide (NO) production are important factors that regulate blood pressure. In this study, the effects of octaphlorethol A (OPA) isolated from Ishige sinicola on ACE inhibition and NO production, the molecular mechanism underlying ACE inhibition, as well as its antihypertensive effect in spontaneously hypertensive rats (SHRs) were investigated. IC50 value of OPA against ACE was 59 µM. Molecular modelling studies indicated that the compound interacts with Cys370, Glu162, Glu376, Glu403, Glu411, Asp377, His383, His387, Tyr520, Arg522, Tyr523, and Lys511. In human endothelial cells, OPA increased endothelial nitric oxide synthase (eNOS) phosphorylation. We also demonstrated that these OPA-induced effects essentially depended on protein kinase B (Akt) and AMP-activated protein kinase (AMPK) activation. Furthermore, systolic blood pressure was reduced (21.9 mmHg in 6 h) by administration of the compound in SHRs. The results of this study suggested that OPA could be developed as a therapeutic agent for hypertension.